Na obrzeżach pola literackiego. Komentarz do Bibliografii przekładów literatury bułgarskiej w Polsce w 2014 roku - Pytlak, Magdalena (Przekłady Literatur Słowiańskich, 2015)
On the margins of literary field. Comment on the Bibliography of literary translations from Bulgarian to Polish in 2014 The paper is a comment on the Bibliography of literary translations from Bulgarian to Polish in 2014. The author of this article focuses on two translations that may be considered as completed — that is, a book with short stories Lomski razkazi (Lom stories) by Emil Andreev and a selection Antologia literatury bułgarskiej w przekładzie Hanny Karpińskiej (Anthology of Bulgarian Literature in translation of Hanna Karpinska). The analysis uses the concept of field and actors/institutions in the literary field by the French sociologist, Pierre Bourdieu. The analysis tries to reveal mechanisms beyond the translation process — decision on what is translated (author and piece), cooperation with publishers, but also official cultural policy of Bulgaria. It also shows differences between book and magazine publications in the context of literary filed (in. al. reading audience, literary prizes). Key words: literary translation, Bourdieu’s field, politics of translation, Bulgarian literature in Poland